2021
DOI: 10.1002/macp.202100283
|View full text |Cite
|
Sign up to set email alerts
|

Oleic Acid Constructed Supramolecular Hyperbranched Polysiloxane with Enhanced Fluorescence and Excellent Drug Delivery Ability

Abstract: Hyperbranched polysiloxane (HBPSi) as a novel unconventional fluorescent polymer has attached great attention due to its stable fluorescence, facile preparation, and good biocompatibility. Study shows that the fluorescence of unconventional fluorescent polymer is closely related to the aggregate state. To promote the aggregate of HBPSi and endow it with drug delivery ability, in this work, different contents of renewable oleic acid are grafted onto a water-soluble HBPSi. Results show that oleic acid constructs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…The fluorescence properties of unconventional fluorescent polymers are closely related to the molecular structure and aggregate morphology. Our research showed that the fluorescence of hyperbranched polysiloxanes could be promoted by introducing L-glutamic acid, 17 beta-cyclodextrin, 18,19 oleic acid, 20 and aromatic amino acids. 21 The introduced small molecules enhanced the intermolecular interactions, including hydrogen bonds, the amphiphilic effect, and N → Si coordination bonds, and then, promoted the polymer aggregation and the interaction among electron-rich atoms, resulting in the formation of spatial electronic delocalizations and enhanced fluorescence.…”
Section: Introductionmentioning
confidence: 83%
“…The fluorescence properties of unconventional fluorescent polymers are closely related to the molecular structure and aggregate morphology. Our research showed that the fluorescence of hyperbranched polysiloxanes could be promoted by introducing L-glutamic acid, 17 beta-cyclodextrin, 18,19 oleic acid, 20 and aromatic amino acids. 21 The introduced small molecules enhanced the intermolecular interactions, including hydrogen bonds, the amphiphilic effect, and N → Si coordination bonds, and then, promoted the polymer aggregation and the interaction among electron-rich atoms, resulting in the formation of spatial electronic delocalizations and enhanced fluorescence.…”
Section: Introductionmentioning
confidence: 83%
“…23−26 Research studies show that the fluorescence intensity and quantum yields could be promoted via decreasing the hindrance between electron-rich atoms/functional groups, 27,28 enhancing the intermolecular hydrogen bonds, 29 increasing the density of electron-rich atoms/functional groups, 17,30 introducing functional groups containing π electrons, 17,30 and adjusting the amphiphilic effect. 32 Moreover, the emission wavelength could also be adjusted.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Besides PAMAM, polymers containing typical groups, such as polyborate, poly­(vinylidene fluoride), poly­(amino ester)­s, organosilicon, polyester, polyethylenimine, as well as natural products, , are emissive under UV light. Investigations show that their emission is closely related to the interaction among electron-rich atoms/functional groups, named clustering-triggered emission (CTE). , The structural features of polymers, such as a hyperbranched structure, linear shape, flexibility, amphiphilicity, chemical groups, molecular weight, etc., affect the fluorescence property. Research studies show that the fluorescence intensity and quantum yields could be promoted via decreasing the hindrance between electron-rich atoms/functional groups, , enhancing the intermolecular hydrogen bonds, increasing the density of electron-rich atoms/functional groups, , introducing functional groups containing π electrons, , and adjusting the amphiphilic effect . Moreover, the emission wavelength could also be adjusted.…”
Section: Introductionmentioning
confidence: 99%
“…In previous work, some researches have studied the relationship between functional groups, backbone, main chain, and the luminescence properties, and found that the introduction of amine group, epoxy group, hydroxyl group, carbonyl group, vinyl group, and hyperbranched structures can significantly improve the fluorescent performance of HBPSi and endow HBPSi with functional applications [19] and achieved cell imaging and controlled drug release by grafting cyclodextrin, glutamic acid, and oleic acid. [20][21][22] However, HBPSi of biological safety has yet to be verified, and most of the currently synthesized HBPSi has common drawbacks such as low fluorescence quantum yield and weak anti-interference, which restricts its potential application in cancer detection and other fields.…”
Section: Introductionmentioning
confidence: 99%